Genetic organization and cellular specificity of S. aureusleukocidins - Bulanin, D.; Marchenko, Ye.A.; Abitayeva, G.K.; Vangelista, L. (Fundamental and Experimental Biology, 2020)
Currently, infections produced by the gram-positive bacteria S. aureusrepresent a significant healthcare burden throughout the world. This is attributed to the ability of this bacterium to develop antibiotic resistance and efficiently evade human immune response. Therefore, research effort of many scientific laboratories worldwide is directed toward characterization of the genetic organization and molecular mechanisms responsible for S. aureuspathogenesis. This report is aimed to describe the growing body of evidence related to our understanding of the genetic organization and molecular interactions of the S. aureus leukocidins with the human cells that play an important role in bacterial pathogenesis, and represent a significant healthcare burden. Understanding of the genetic organization linked with additional mechanisms responsible for the realization of toxic potential, can help us to develop a better personalized approach for therapy against S. aureus infections. Thus, improved understanding of the molecular interactions betweenS. aureusleucocidins, and cell surface receptors may lead to the development of the alternative anti-microbial agents, that either independently or in combination with the current antibiotic treatment regimens will be used as an effective treatment strategy in clinic.